Retail spatial organisation and the physical city: bridging retail geography and urban morphology - Alessandro Araldi; Benjamin Wayens; Giovanni Fusco (Belgeo)
The spatial organization of stores plays a crucial role in the production and development of the urban form while, at the same time, being strongly influenced from the physical constraints of the latter. Yet the connection between retail distribution and the physical form of cities remains underexplored. This paper aims to unify the perspectives of two distinct disciplines—retail geography and urban morphology—rooted in the late 19th and early 20th centuries. Retail geography, tracing its origins to classical works in American and German regional economics, and urban morphology, emerging from the convergence of architectural and geographical schools in England, Italy and France, have evolved independently since the late '60s. This paper reviews their development, highlighting theoretical and empirical studies elucidating the interrelationship between retail distribution and urban form. While both disciplines acknowledge the mutual influence of retail and cities, they have progressed independently, with retail geography focusing on the evolution of the retail sector and urban morphology emphasizing the impact of physical form on socioeconomic functions. Identifying common ground, this paper underscores spatial affinities and organizational aspects often overlooked. The paper concludes by encouraging a unified understanding, recognizing the potential for a more nuanced comprehension of the intricate dynamics between retail distribution and the physical features of cities. This approach paves the way for future interdisciplinary research, fostering collaboration in unravelling the complexities that shape urban environments.